1976
DOI: 10.1113/jphysiol.1976.sp011247
|View full text |Cite
|
Sign up to set email alerts
|

The contractile state of rabbit papillary muscle in relation to stimulation frequency.

Abstract: SUMMIARY1. The relationship between active force and stimulation frequency (0-25--5/sec) was studied at 36-37o C in isolated papillary muscles of the rabbit.2. The muscle's force producing capability at a given frequency was determined as the isometric twitch response to a test stimulus that was applied at various times after a priming period. The optimum contractile response was obtained at an interval of 0-8 sec between the test pulse and the last stimulus of the priming period.3. The optimum contractile res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
71
1

Year Published

1979
1979
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(83 citation statements)
references
References 26 publications
11
71
1
Order By: Relevance
“…The maximum developed pressure at Volmax, 99.9-150.2 mmHg, corresponds to the maximum wall stress, 20.0-37.8 mN/mm2 (28.2+5.6 mN/mm2) at Lmax, which should be the muscle length at Volmax. These estimated values are comparable with the maximum force obtained in the rabbit papillary muscle which is about 25 mN/mm2 at 95 % Lmax at 2 Hz stimulation (EDMAN and JOHANNSSON, 1976). The active stress in the wall muscle was found to be 6.2+2.1 (3.4-9.4) times greater than resting stress at Lmax, that is, the ratio of resting-tototal stress was 15.4±4.8% (10-23 %).…”
Section: Discussionsupporting
confidence: 83%
“…The maximum developed pressure at Volmax, 99.9-150.2 mmHg, corresponds to the maximum wall stress, 20.0-37.8 mN/mm2 (28.2+5.6 mN/mm2) at Lmax, which should be the muscle length at Volmax. These estimated values are comparable with the maximum force obtained in the rabbit papillary muscle which is about 25 mN/mm2 at 95 % Lmax at 2 Hz stimulation (EDMAN and JOHANNSSON, 1976). The active stress in the wall muscle was found to be 6.2+2.1 (3.4-9.4) times greater than resting stress at Lmax, that is, the ratio of resting-tototal stress was 15.4±4.8% (10-23 %).…”
Section: Discussionsupporting
confidence: 83%
“…We previously reported that the peculiar force-frequency relationship in rat atria was differently affected by aand P-adrenoceptor stimulation, especially at a higher range of stimulation rates (Hattori & Kanno, 1984). Complexly intertwined processes, sometimes acting in opposite directions, determine the actual tension developed at a constant stimulation rate (Chapman, 1979), and changing the stimulation interval may unmask a fundamental step ofcellular Ca2" dynamics (Allen et al, 1976;Edman & J6hannsson, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…The latter site provides the activator Ca to be released by the following action potential. Such a process has been postulated mainly in the mammalian myocardium, especially in regard to the Woodworth type staircase phenomenon (WOOD et al, 1969;MORAD and GOLDMAN, 1973;EDMAN and JOHANNSON, 1976).…”
Section: Discussionmentioning
confidence: 99%